SEDIMENT STRATIGRAPHY IN COASTAL WATERS OF WESTERN PART OF RUPAT STRAIT RIAU PROVINCE - Rinu Maido; Rifardi '; Bintal Amin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The study aims to describe Lithostratigraphy based on verticaldistribution of sediment fractions in western part of Rupat Strait. The sedimentsamples were taken in May 2014 from 9 sampling points and 3 stations by usinggravity cores. The position of the sampling point was determined by usingpurposive sampling method. Each sample obtained from core samples wasdivided into 3. All the sediment samples were analyzed by using mechanicalanalysis. The analysis showed that the sediment in the area was dominated by thesand fraction with percentages ranging from 58.59 to 98.31 % with the highestpercentage was located at the sampling point 2 middle layer and the lowest at 5sampling points lower layers. Sediment grain size did not undergo significantdifference vertically. At station 1 the changes in sediment grain size was onlyfound at the sampling point 3 middle layer. Sediment grain size at station 2changed at the sampling point 4 middle layer and the top layer 6 sampling pointswhile the grain size of the sediment contained in station 3 occurs at the samplingpoint 7 layers above and below the layer 9 sampling points. Based on clusteranalysis the sediment layer of western part of Rupat strait IV can be divided intogroups based on five characteristics of sediments and in each group showed thatthe difference was not significant.Keywords : Stratigraphy, Sedimentary, Rupat Strait